We have experimented with different approaches to systems transformati on — here are five insights - Haldrup, Søren Vester (2021)
At UNDP Innovation we are on a journey to shift our approach to innova tion to help tackle complex development challenges. In short, we are m oving away from single point solutions, and instead we are…